Intimate relationships and patterns of drug and sexual risk behaviors among people who inject drugs in Kazakhstan: A latent class analysis. (1st November 2018) - Marotta, Phillip L.; Terlikbayeva, Assel; Gilbert, Louisa; Hunt, Tim; Mandavia, Amar; Wu, Elwin; El-Bassel, Nabila
Highlights: Latent class analysis on sexual and drug HIV risks among PWID in Kazakhstan. Identified 3 underlying latent classes of low, medium, and high HIV risk behavior. Similar latent class structure between men, women and overall. Shorter relationship length associated with medium-risk class membership for men. Low risk reduction self-efficacy associated with high/medium class for women. Abstract: Background: Multiple drug and sexual risk behaviors among people who inject drugs (PWID) in intimate relationships increase the risk of HIV and HCV transmission. Using data on PWID in intimate partnerships in Almaty, Kazakhstan, this study performed latent class analysis (LCA) on drug and sexual risk behaviors and estimated associations between dyadic relationship factors and membership in latent classes. Methods: LCA was performed on a sample of 510 PWID (181-females/FWID, 321-males/MWID) to identify levels of drug and sexual risk behaviors. Generalized structural equation modeling with multinomial regressions estimated associations between relationship factors (length risk reduction communication, risk reduction self-efficacy) and class membership after adjusting for substance use severity, overdose, depression, binge drinking, intimate partner violence, structural factors, and sociodemographic characteristics. Models were sex-stratified to include FWID and PWID. Results: A 3-class model best fit the data and consisted of low, medium, and high-risk classes. GSEM found that greater injection self-efficacy was associated with a lower likelihood of membership in the high-risk class for PWID and FWID. For MWID, greater length of the relationship was associated with a lower likelihood of membership in the medium-risk class. Greater relationship communication was associated with increased risk of membership in the high-risk latent class for MWID. Conclusions: Future research must investigate if increasing risk reduction and safe sex self-efficacy could reduce drug and sexual risk behaviors and HIV transmission among PWID and their intimate partners. Interventions are needed that reduce power inequities within relationships as a method of increasing self-efficacy, particularly among women.